An mHealth Intervention (ReZone) to Help Young People Self-Manage Overwhelming Feelings: Cluster-Randomized Controlled Trial - Edridge, Chloe (J Med Internet Res, 2020)
BACKGROUND: Mental health difficulties in young people are increasing, and there is a need for evidence on the effectiveness of digital interventions to increase opportunities for supporting mental health in young people. Such studies are complicated due to issues of implementation and adoption, outcome measurement, and appropriate study designs. OBJECTIVE: The objective of this study was to examine the effectiveness of an mHealth intervention (ReZone) in reducing mental health difficulties in young people. METHODS: The cluster-randomized controlled trial enrolled 409 participants aged 10-15 years, and classes were allocated to ReZone or management as usual. Self-reported questionnaires were completed at baseline and 3-month follow-up. RESULTS: There were no significant differences between the ReZone condition and management as usual in the self-reported outcome measures. However, there were 3467 usage sessions, which corresponds to 16.9 times per student (total of 205 students) in classes allocated to ReZone. CONCLUSIONS: It is essential to publish studies that do not show significant differences, as these findings can still contribute to the literature, help in learning, and inform the direction of future work. The results reported in this paper could be due to a range of reasons, including whether ReZone has the scope to impact change or limitations related to the setting, context, and appropriateness of an RCT. The findings of this study suggest that ReZone was implemented and adopted. INTERNATIONAL REGISTERED REPORT IDENTIFIER (IRRID): RR2-10.2196/resprot.7019